Correlation of Chronic Neck Pain with ADLs, Sleep, and Work Family Conflict in Female School Teachers (International Journal of Physiotherapy, 2025)
Background: Related to work, musculoskeletal disorders mainly cause the burden of occupational diseases. Particularly those who work in desk jobs, such as computer workers and female school teachers, are more susceptible to these conditions. Female educators face a range of health issues as a result of their physical and psychological workloads, with neck discomfort being a major one. This research aims to correlate chronic neck pain with ADLs, sleep, and workfamily conflict in female school teachers.Materials and Methods: The study included 188 female school teachers with at least three years of work experience and persistent neck discomfort for two months. The Subjects fulfilling the inclusion and exclusion criteria were administered the outcome measures such as the Pittsburgh Sleep Quality Index (PSQI), Northwick Park Neck Pain Questionnaire (NPNPQ), Numeric Pain Rating Scale (NPRS), and Work and Family Conflict Scale (WAFCS).Results: The correlation coefficient ("r") showed that the numeric pain rating scale, NPNPQ, PSQI, and WAFCS were positively correlated (p